PENERAPAN MEDIA PEMBELAJARAN BoneLab UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Siti Rabiatul Fajri; Titi Laily Hajiriah; Islahiyah Islahiyah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
This study aims: 1) to find out the increase in student learning outcomes; and 2) to find out students' responses after applying BoneLab learning media in class VIII at MTs. Nahdlatul Mujahidin NW Jempong. The research method uses Classroom Action Research (CAR), which consists of 2 cycles, each cycle containing the stages of preparation, implementation, observation, and reflection. The research instruments consisted of: 1) teacher observation sheet activity; 2) student observation sheet activity; 3) learning achievement test sheets; and 4) student questionnaire response sheets. The data analysis technique used is quantitative descriptive analysis with percentages. The results of the study stated that, the activities of teachers in the first cycle carried out